Performing Multiple Posterior Spinal Fusions in 1 Day: A Comparison of Perioperative Outcomes Between Morning and Afternoon Cases. Issue 9 (2nd October 2021) - O'Neill, Nora P.; Hedequist, Daniel J.; Glotzbecker, Michael; Cook, Danielle; Yang, Troy; McCann, Mary E.; Chacko, Sabeena; Cravero, Joseph; Hresko, Michael Timothy
Abstract : Background: High-volume centers for idiopathic scoliosis (IS) have difficulty in scheduling posterior spinal fusions (PSFs) due to operating room availability, particularly during school vacation. A solution is for 1 surgeon to perform 2 PSF cases back-to-back. This study aims to compare morning and afternoon PSF cases performed by the same surgeon for perioperative outcomes. Methods: A retrospective review of PSF cases for IS that occurred on the same day as another PSF by the same surgeon between January 2013 and December 2019 was conducted. Perioperative outcomes included surgical time, estimated blood loss, length of stay, and inpatient opioid consumption normalized by the patient's weight. Postoperative outcomes included complications, revision rate, curve correction, and patient-reported outcomes using the Scoliosis Research Society-30. Results: A total of 95 patients (87% female), mean age 15.6 years, were analyzed, with 48 morning cases and 47 afternoon cases. The median follow-up was 1.9 years (range: 0.3 to 6.1 y). Tests for equivalency determined equivalence in median anesthesia and mean surgical duration ( P =0.05). The groups had similar initial curve correction ( P =0.43) and rate of complications at 90 days postoperative (2 in each group for a total of 4 complications). No significant differences were seen between Scoliosis Research Society-30 scores at 6 months or in those who have reached 2 years postoperative. Conclusions: Little literature exists on the safety of a surgeon performing 2 PSF cases in 1 day, particularly in regard to pain outcomes, 30- and 90-day complication rates, and quality of life measures. This study indicates that few differences in safety, pain, and quality of life outcomes may appear between morning and afternoon PSF cases. Level of Evidence: Level II.